Naturally occurring radioactive materials and related hazard indices in Ahdeb oil field - Hassan, Zainab Mohammed (Iraqi Journal of Physics, 2019)
In this work, measurements of activity concentration of naturally occurring radioactive materials (NORM) isotopes and their related hazard indices for several materials such as crude oil, sludge and water in Ahdeb oil fields in Waste governorate using high pure germanium coaxial detection technique. The average values for crude oil samples were174.72Bq/l, 43.46Bq/l, 355.07Bq/l, 264.21Bq/l, 122.52nGy/h, 0.7138, 1.1861, 0.601 mSv/y, 0.1503mSv/y and 1.8361 for Ra-226, Ac-228, K-40, Ra eq, D, H-external and H-internal respectively. According to the results; the ratio between 238U to 232Th was 4, which represents the natural ratio in the crust earth; therefore, one can be strongly suggested that the geo-stricture of the Ahdeb oil fields dose not contents any kind of rocks. Although the results indicate the rising in the activity concentration of NORM isotopes, the national and international comparisons proved that it is still in the world range limits.